Evaluating Clinical Educators' Competence in an East Asian Context: Who Values What? - Jenq, Chang-Chyi; Ou, Liang-Shiou; Tseng, Hsu-Min; Chao, Ya-Ping; Lin, Jiun-Ren; Monrouxe, Lynn V. (Frontiers in Medicine, 2022)
Background: How to evaluate clinical educators is an important question in faculty development. The issue of who are best placed to evaluate their performance is also critical. However, the whos and the hows of clinical educator evaluation may differ culturally. This study aims to understand what comprises suitable evaluation criteria, alongside who is best placed to undertake the evaluation of clinical educators in medicine within an East Asian culture: specifically Taiwan. Methods: An 84-item web-based questionnaire was created based on a literature review and medical educational experts’ opinions focusing on potential raters (i.e. who) and domains (i.e. what) for evaluating clinical educators. Using purposive sampling, we sent 500 questionnaires to clinical educators, residents, Post-Graduate Year Trainees (PGYs), Year-4~6/Year-7 medical students (M4-6/M7) and nurses. Results: We received 258 respondents with 52% response rate. All groups, except nurses, chose "teaching ability" as the most important domain. This contrasts with research from Western contexts that highlights role modelling, leadership and enthusiasm. The clinical educators and nurses have the same choices of the top five items in the “personal qualities” domain, but different choices in “assessment ability" and “curriculum planning” domains. The best fit rater groups for evaluating clinical educators were educators themselves and PGYs. Conclusions: There may well be specific suitable domains and populations for evaluating clinical educators’ competence in East Asian culture contexts. Further research in these contexts is required to examine the reach of these findings.